IMPLEMENTASI DAN TATA KELOLA SINERGI PROGRAM HIV–TBC DI KABUPATEN CIREBON: ANALISIS CAPAIAN, HAMBATAN, DAN ARAH PENGUATAN LAYANAN TERPADU - Awaludin; Putri Isriyatil Jannah; Puji Melati (Journal of Health Service Management, 2026)
Background: The integration of HIV and tuberculosis (TB) services is a key strategy to achieve communicable disease elimination targets. At the subnational level, the effectiveness of integration is strongly influenced by governance capacity, continuity of care, and interoperability of health information systems. Cirebon District has established a local regulatory framework for HIV–TB collaboration; however, its implementation and performance remain suboptimal. Objective: This study aimed to analyze the performance, barriers, and governance of HIV–TB program synergy in Cirebon District during 2024–August 2025 and to identify directions for strengthening integrated services. Methods: This study employed a convergent parallel mixed-methods design, integrating descriptive quantitative analysis of routine program data with qualitative thematic content analysis. Program performance data were obtained from the HIV/AIDS Information System (SIHA), the Tuberculosis Information System (SITB), and the Public–Private Mix for TB Control (PHTC) dashboard. Policy implementation was examined through a review of Regent Regulation No. 33/2016 and semi-structured interviews with key program managers and service providers. Quantitative and qualitative findings were analyzed concurrently and integrated at the interpretation stage. Results: HIV testing coverage exceeded 100% of the target among groups integrated into routine health services, such as pregnant women (103.2%), but was lower among tuberculosis (TB) patients (84.7%) and markedly low among stigmatized populations, including transgender individuals (52.0%) and people who inject drugs (33.3%). The cumulative number of people living with HIV/AIDS continued to rise, reaching 3,960 cases by 2025, with 492 new cases reported in 2024. The HIV–TB cascade analysis revealed that only 46.8% of TB patients were recorded as having undergone HIV testing. A total of 28 HIV–TB patients (approximately 0.6% of all TB patients) were identified, and all initiated antiretroviral therapy; however, no patients received tuberculosis preventive therapy (TPT). Fragmentation between the SIHA and SITB information systems, along with weak cross-program coordination, undermined continuity of care. Conclusions: HIV–TB program synergy in Cirebon District is constrained primarily by weaknesses in governance and health system integration rather than by a lack of clinical services. Strengthening operational integration, data interoperability, and performance-based supervision is essential to ensure that expanded HIV testing and treatment translate into measurable reductions in HIV–TB transmission and mortality.